Looking at the future of the medical certification of cause of death (MCCD) in England and Wales - Millares Martin, Pablo; Allsop, Matthew J.; Carder, Paul (International journal of legal medicine, 2024)
Internationally, the quality of death certification is poor although there are multiple efforts underway to improve the process. In England, a new medical certification system has been proposed to improve the quality of data. We surveyed general practitioners ( n = 95) across the West Yorkshire area of England to appraise their views regarding whether further possible changes to the death certification system could promote their quality.